Point-of-care testing, antibiotic prescribing, and prescribing confidence for respiratory tract infections in primary care: a prospective audit in 18 European countries - van der Velden, Alike W; van de Pol, Alma C; Bongard, Emily; Cianci, Daniela; Aabenhus, Rune; Balan, Anca; Böhmer, Femke; Bralić Lang, Valerija; Bruno, Pascale; Chlabicz, Slawomir; Coenen, Samuel; Colliers, Annelies; et al. (BJGP open, 2022)
Between-country differences have been described in antibiotic prescribing for RTI in primary care, but not yet for diagnostic testing procedures and prescribing confidence. To describe between-country differences in RTI management, particularly diagnostic testing and antibiotic prescribing, and investigate which factors relate to antibiotic prescribing and GPs' prescribing confidence. Prospective audit in 18 European countries. GPs registered patient-, clinical- and management characteristics, and confidence in their antibiotic prescribing decision for patients presenting with sore throat and/or lower RTI (n=4,982). Factors related to antibiotic prescribing and confidence were analysed using multi-level logistic regression. Antibiotic prescribing proportions varied considerably:<20% in four countries, and >40% in six countries. There was also considerable variation in POC testing (0% in Croatia, Moldova, Romania, and >65% in Denmark, Norway, mainly CRP and Strep A), and in lab/hospital-based testing (<3% in Hungary, Netherlands, Spain, and >30% in Croatia, Georgia, Greece, Moldova, mainly chest X-ray and white blood cell counting). Antibiotic prescribing was related to illness severity, comorbidity, age, fever and 'country', but not to having performed a POC test. In nearly 90% of consultations, GPs were confident in their antibiotic prescribing decision. Despite high confidence in decisions about antibiotic prescribing, there is considerable variation in the primary care of RTI in European countries, with GPs prescribing antibiotics overall more often than is considered appropriate. POC testing may enhance the quality of antibiotic prescribing decisions if it can safely reverse decisions confidently made on clinical grounds alone to prescribe antibiotics.